1991
DOI: 10.1007/bf03258312
|View full text |Cite
|
Sign up to set email alerts
|

Action of Nimesulide on Rat Gastric Prostaglandins and Renal Function

Abstract: SummaryNimesulide, a nonsteroidal anti-inflammatory drug (NSAID), was shown to be less ulcerogenic [dose inducing ulceration in 50% of rats (UDso) > 20 mg/kg orally] than indomethacin (UDso = 1.6 mg/kg orally) and, in contrast to indomethacin, to affect prostaglandin E2 (PGE2) [dinoprostone] and thromboxane A2 (TXA2) formation more potently in inflammatory exudate than in the gastric mucosa in rats.After administration for 3 consecutive days, nimesulide in doses of up to 9 mg/kg orally (about 7 times the anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
12
0
1

Year Published

1997
1997
2005
2005

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 25 publications
4
12
0
1
Order By: Relevance
“…The present findings lend support to the growing number of reports (34)(35)(36)(37)(38)(39)(40)(41) demonstrating that NSAIDs, particularly certain COX-2 inhibitors of the sulfonamide class (NIM, NS-398), exert specific biologic activities other than the simple inhibition of COX activity and release of prostaglandins. We believe that these latter effects, which we have defined as "allo-effects," could contribute to the overall therapeutic efficacy of the drugs.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The present findings lend support to the growing number of reports (34)(35)(36)(37)(38)(39)(40)(41) demonstrating that NSAIDs, particularly certain COX-2 inhibitors of the sulfonamide class (NIM, NS-398), exert specific biologic activities other than the simple inhibition of COX activity and release of prostaglandins. We believe that these latter effects, which we have defined as "allo-effects," could contribute to the overall therapeutic efficacy of the drugs.…”
Section: Discussionsupporting
confidence: 85%
“…Nimesulide (NIM) is a preferential inhibitor of COX-2 activity with marked biologic effects in several in vivo models of inflammation (32)(33)(34)(35)(36). Results of a number of studies have suggested that, in addition to the well-described inhibition of prostaglandin synthesis, NIM exerts pleiotropic effects, particularly in terms of neutrophil function (e.g., respiratory burst) (37)(38)(39).…”
mentioning
confidence: 99%
“…Tofanetti et al [37] had demonstrated that a single oral administration of nimesulide, in contrast to a single oral administration of indomethacin, decreased PGE 2 and thromboxane (TX) B 2 synthesis more potently in inflammatory exudates caused by carrageenan cotton pellet implants, now known to be a COX-2-dependent synthesis, than in the gastric mucosa, now known to be COX-1-dependent. Their results indicate an average COX-2/COX-1 ratio of 0.08 and were corroborated by Ceserani et al [38] who demonstrated that in rats, the nimesulide dosage inducing ulceration in 50% of the animals (UD50) was higher than 20 mg.kg ¹1 orally versus 1.6 mg.kg ¹1 orally for indomethacin. Tanaka et al [39] also showed that nimesulide (UD50 ¼ 106 mg. kg ¹1 ) is better tolerated by rats than indomethacin (UD50 ¼ 2.9 mg.kg ¹1 ), piroxicam (UD50 ¼ 6.7 mg.kg ¹1 ) and ibuprofen (UD50 ¼ 81 mg.kg ¹1 ).…”
Section: Animal Pharmacological Data Obtained With Nimesulidesupporting
confidence: 72%
“…The pharmacological profile of nimesulide in animals suggested that it might be an NSAID with selective inhibitory activity on COX-2 [37][38][39][40][41][42]. Since 1994, several groups have shown, in vitro [35, 43, 44, 46, 47, 51, 53, 54, 56-58, 64, 66] and in one human in vivo model [65], that nimesulide demonstrates a good selectivity as a COX-2 inhibitor.…”
Section: Animal Pharmacological Data Obtained With Nimesulidementioning
confidence: 99%
“…К ним относятся: подавление генерации нейтрофи-лами свободных кислородных радикалов, ингибиция актив ности коллагеназы, повреждающей хрящ, подавление вы работки фактора некроза опухоли -альфа, гистамина, ин терлейкина-6, эластазы [5]. Целый ряд клинических иссле дований продемонстрировал высокую эффективность ни мулида, сравнимую с классическими НПВП (диклофенак, напроксен, пироксикам, кетопрофен) при заболеваниях ко стно-суставной системы, хирургической патологии, тром бофлебите и других нозологиях [6].В то же время в экспериментах на животных было вы явлено, что доза нимулида, индуцирующая развитие язвен но-эрозивного повреждения Ж КТ, во много раз превыша ет таковую для индометацина (> 20 м г/кг и 1,6 мг/кг -со ответственно) [8]. В том же исследовании показано отсут ствие клинически значимых нарушений лабораторных по казателей, отражающих функцию почек, или изменений концентрации почечной ф ракции простагландина Е2 при назначении нимулида в дозе до 9 мг/кг.…”
unclassified